Hoja med knjigami, pohajkovanje po knjižnici in Faldbakknova kaotična gnezda knjig - Škerlj, Nena (Knjižnica, 2019)
The library is presented here as a space for focussed walking in the search for a certain book and/or a space for strolling among books; it can be a space of order and/or disorder, in both cases being a space of beauty and potential creativity. Various ways of systematising knowledge have always been present, while the emphasis on disorder in order is more characteristic of the recent times. For example, Matias Faldbakken, Jorge Louis Borges, Alberto Manguel and many others have addressed these issues and highlighted the importance and beauty of the unordered order within the cosmos, the world, libraries and books.
Keywords: arhitektura; estetika; Faldbakken, Matias; instalacije (umetnost); knjižnice; knjižnični prostori; sistematizacija